PERTUMBUHAN TANAMAN CAISIM (Brassica chinensis var. Parachinensis) DENGAN PEMBERIAN VARIASI DOSIS PUPUK KANDANG AYAM - Jesica Berdame; Jantje Pongoh; Maria G.M. Polii; Meity Rantung; Paula Supit; Saartje Sompotan (Universitas Sam Ratulangi, 2024)
Caisim (Brassica chinensis var. Parachinensis) is a type of vegetable that is in great demand by the public, because it contains many nutrients that humans need. Using chicken manure on caisim plants to provide nutrients for plant survival and growth. This research aims to see and determine the growth response of caisim plants (Brassica chinensis var. Parachinensis) by administering varying doses of chicken manure. This research was carried out in Sea Village, Pineleng District, Minahasa North Sulawesi from January to February 2023.This research used a completely randomized design (CRD) method with varying doses of chicken manure, with chicken manure needs are : Without treatment (A0), 312,5 grams/ polybag (A1), 625 grams/ polybag (A2), 937,5 grams/ polybag (A3). Data analysis from the observations was analyzed using Analysis of Variance (ANOVA) and continued with the Least Significant Difference Test (LSD) with unequal replications.From the research result, the caisim plant lacks light in the plant growth process. The hypothesis was also rejected because varying doses of chicken manure had no effect on the growth and development of the caisim plant. It is recommended to choose an ideal research location for succes in the cultivation process, the importance of the need for sunlight in plant growth to influence photomorphogenesis, namely plant growth and development which is directly controlled by sunlight. Keywords : caisim, dosages of chicken manure